Statin Treatment Is Associated with Reduction in Serum Levels of Receptor Activator of NF-κB Ligand and Neutrophil Activation in Patients with Severe Carotid Stenosis. (6th February 2014) - Lenglet, Sébastien; Quercioli, Alessandra; Fabre, Mathias; Galan, Katia; Pelli, Graziano; Nencioni, Alessio; Bauer, Inga; Pende, Aldo; Python, Magaly; Bertolotto, Maria; Spinella, Giovanni; Pane, Bianca; et al.
Abstract : Systemic and intraplaque biomarkers have been widely investigated in clinical cohorts as promising surrogate parameters of cardiovascular vulnerability. In this pilot study, we investigated if systemic and intraplaque levels of calcification biomarkers were affected by treatment with a statin in a cohort of patients with severe carotid stenosis and being asymptomatic for ischemic stroke. Patients on statin therapy had reduced serum osteopontin (OPN), RANKL/osteoprotegerin (OPG) ratio, and MMP-9/pro-MMP-9 activity as compared to untreated patients. Statin-treated patients exhibited increased levels of collagen and reduced neutrophil infiltration in downstream portions of carotid plaques as compared to untreated controls. In upstream plaque portions, OPG content was increased in statin-treated patients as compared to controls. Other histological parameters (such as lipid, macrophage, smooth muscle cell, and MMP-9 content) as well as RANKL, RANK, and OPG mRNA levels did not differ between the two patient groups. Serum RANKL/OPG ratio positively correlated with serum levels of neutrophilic products, intraplaque neutrophil, and MMP-9 content within downstream portions of carotid plaques. In conclusion, statin treatment was associated with improvement in serum RANKL levels and reduced neutrophil activity both systemically and in atherosclerotic plaques.